Antibody-Based Targeting of Interferon-Beta-1a Mutein in HER2-Positive Cancer Enhances Antitumor Effects Through Immune Responses and Direct Cell Killing - Lee, Chan Gyu; Kim, TaeEun; Hong, Sungyoul; Chu, Jongwan; Kang, Ju Eun; Park, Hee Geon; Choi, Jun Young; Song, Kyoung; Rha, Sun Young; Lee, Soohyeon; Choi, Joon-Seok; Kim, Sun Min; et al. (Frontiers in Pharmacology, 2021)
Type I interferon (IFN) has been approved as an anticancer agent to treat some malignancies. However, IFNs have a short in vivo half-life, systemic toxicity, and poor biophysical properties, which prevent it from being widely used for cancer therapy. This study aimed to construct recombinant IFN--1a mutein immunocytokines that comprise a human epidermal growth factor receptor 2 (HER2)-targeting antibody and IFN- muteins with an additional glycosylation, which can overcome the limitation of the cytokine itself. Hence, the molecular design aims to (i) enhance productivity and biophysical properties by adding secondary glycosylation in IFN-, (ii) increase the therapeutic index of IFN- therapy by preferential retention at the tumor by possessing high affinity for HER2-expressing cancer cells, and (iii) improve the pharmacokinetics and, thus, the convenience of IFN-administration. The yield of trastuzumab-IFN- mutein was higher than that of trastuzumab-wild-type IFN- in the mammalian cell culture system. Trastuzumab-IFN- mutein showed similar IFN activity and HER2-targeting ability equivalent to that of IFN- mutein and trastuzumab, respectively. Trastuzumab-IFN- mutein directly inhibited the growth of HER2-positive gastric cancer cell lines and was more effective than trastuzumab or IFN- mutein alone. Trastuzumab-IFN- mutein and IFN- mutein displayed enhanced immune cell-mediated cytotoxicity. Collectively, trastuzumab-IFN- mutein may have indirect immune cell-mediated antitumor effects and direct cell growth inhibitory effects. The biodistribution of trastuzumab-IFN- mutein was analyzed using in vivo fluorescence imaging. The accumulation of trastuzumab-IFN- mutein was observed in HER2-positive tumors rather than other tissues except the liver. To evaluate the both direct tumor growth inhibition effect and indirect immune cell-mediated antitumor effect, we tested the effect of trastuzumab-IFN- mutein in HER2-positive cancer xenograft models using nude mice or humanized mice. Trastuzumab-IFN- mutein could significantly enhance tumor regression when compared with trastuzumab or IFN-mutein. In addition, an increase in tumor-infiltrating lymphocytes was observed in the trastuzumab-IFN-mutein-treated group, implying that the tumor-targeting IFN- may have an enhanced antitumor effect through increased immune response. Therefore, targeting IFN- with an anti-HER2 monoclonal antibody makes the immunocytokine more potent than either agent alone. These novel findings suggest that trastuzumab-IFN- mutein merits clinical evaluation as a new candidate of anticancer therapeutics.